Actinidia chinensis Planch.: A Review of Chemistry and Pharmacology - He, Xirui; Fang, Jiacheng; Chen, Xufei; Zhao, Zefeng; Li, Yongsheng; Meng, Yibing; Huang, Linhong (Frontiers in Pharmacology, 2019)
Actinidia chinensis Planch., (A. chinensis) commonly known as Chinese kiwifruit, is a China native fruit, which becomes increasingly popular due to attractive economic, nutritional and health benefits properties. The whole plant including fruits, leaves, vines and roots of A. chinensis are used mainly as food or additive in food products and as folk medicine in China. It is a good source of triterpenoids, polyphenols, vitamin C, carbohydrate, amino acid and minerals. These constituents render the A. chinensis with a wide range of pharmacological properties including antitumor, antioxidant, anti-inflammatory, immunoregulatory, hypolipemic, antidiabetic, and cardiovascular protective activities, suggesting that it may possibly be value in the prevention and treatment of pathologies associated to cancer, oxidative stress and aging. This mini-review provide a brief knowledge about the recent advances in chemistry, biological activities, utilization and storage of Chinese kiwifruit. Future research directions on how to better use of this crop are suggested.